Dualisme Kewenangan Pemeriksaan Dugaan Pelanggaran Kode Etik Notaris - Muhammad Khalid (Lex Renaissance, 2017)
AbstractProblems in the study: first, the dualism of authority checks Notary alleged violations of the code of conduct? Second, the authority checks the code of conduct by the Regional Supervisory Council based on the code of ethics? This research is empirical jurisdiction. The study concluded, first, the Regional Supervisory Council and the WCA Board may conduct an examination of the alleged violations of the code etik Notaris. Regional Supervisory Council code etik Notaris checks if the report from the public and there is also a certain criteria of Notaries code violations that can be checked by the Supervisory Council of Regions. Honorary Board area is not just waiting for reports received, but can process it if it finds violations of the code of conduct, if the Honorary Board of the Regional found violations of the Code, the Honor Council will call a notary in question to be fostered, because the function of the Honorary Council of Regions in addition to overseeing the code of conduct, there is pembianaan also against the Notary. Code violations that have been reported to the Regional Supervisory Council can not be diverted report to the Council of Honor, and vice versa. Secondly, the provision of the code of conduct by the inspection authority Regional Supervisory Council is not in accordance with the characteristics of the code of professional conduct.Keywords: Regional Supervisory Council, Notary.